Do hydrologic rigor and technological advance tell us more or less about transboundary water management? - Giordano, Mark; Suhardiman, Diana; Peterson-Perlman, J. (Springer, 2016)
Strict hydrologic definitions of basins coupled with technological advances including the use of remote sensing and geographic information systems have given us more accurate and detailed knowledge than ever before about the scale and extent of transboundary waters. This information has had both research and policy impact. The knowledge of the vast number and extent of basins has been used to bring attention to the overall issue of transboundary water management and understand how and why countries conflict and cooperate over water. Combining this information with ideas embedded in legal instruments such as the UN Convention on the Law of the Non-Navigational Uses of International Watercourses has given us new ways to look at the adequacy, and inadequacy, of existing transboundary institutions and to suggest policy change and institution building. But do precise data and clearly codified definitions always improve our understanding and decision making? Might they even lead us to incorrect conclusions and poor priority setting? This paper examined how the combination of universalized basin scale principles for international water management and increased mapping precision has resulted in policy prescriptions that sometimes run counter to what negotiators and managers have consistently and thoughtfully done in practice. The conclusion is not a call to cease using new technology nor to end the search for principles to guide our resource management actions. Rather it is a call for caution and balance as we apply technology and logic to specific locations in a complex world.